Multilevel modelling of factors influencing eight or more antenatal care visits among women of reproductive age in South Africa - Mashapa M. Malatji; Mluleki Tsawe (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Globally, thousands of women die due to pregnancy-related complications. The World Health Organization recommends at least eight or more antenatal visits during pregnancy to reduce infant and maternal mortality. This study examined the factors influencing eight or more antenatal visits among South African women aged 15-49, using data from the 2016 South Africa Demographic and Health Survey (weighted sample of 3036 women). A two-level binary logistic regression model was used to identify the factors determining the use of eight or more antenatal visits. The findings revealed a low use (17.1%) of eight or more antenatal care visits. Age at birth, birth order, population group, marital status, employment status, media exposure, place of residence, household wealth and province were statistically associated with eight or more antenatal care visits. Women whose age at birth was 20-34, those exposed to the media, those from rich households, and those from the Western Cape had higher odds of eight or more antenatal care visits. Media campaigns may play a valuable role in informing women about the advantages of attending the recommended antenatal care visits.Globally, thousands of women die due to pregnancy-related complications. The World Health Organization recommends at least eight or more antenatal visits during pregnancy to reduce infant and maternal mortality. This study examined the factors influencing eight or more antenatal visits among South African women aged 15-49, using data from the 2016 South Africa Demographic and Health Survey (weighted sample of 3036 women). A two-level binary logistic regression model was used to identify the factors determining the use of eight or more antenatal visits. The findings revealed a low use (17.1%) of eight or more antenatal care visits. Age at birth, birth order, population group, marital status, employment status, media exposure, place of residence, household wealth and province were statistically associated with eight or more antenatal care visits. Women whose age at birth was 20-34, those exposed to the media, those from rich households, and those from the Western Cape had higher odds of eight or more antenatal care visits. Media campaigns may play a valuable role in informing women about the advantages of attending the recommended antenatal care visits.